HUBUNGAN SELF EFFICACY DAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI SISTEM PERSAMAAN LINIER TIGA VARIABEL - Wari Purnama Sari; Halini Halini; Dian Ahmad BS (UNIVERSITAS TANJUNGPURA, 2023)
This study's objective is to ascertain whether A connection exists between students' math learning results on the subject include linear equations with three elements and their level of self-efficacy. The study used a sample of 20 students, which was carried out in September 2022. Correlation approaches were employed in a survey as the study methodology. Data were gathered using student math learning outcomes and self-efficacy instruments. The instrument's reliability and validity have been assessed., making it both valid and dependable. The answers of the self-efficacy questionnaire and the findings of the description were found to be regularly distributed using Lilliefors' prerequisite testing of normality. If the information is evenly distribute, a linearity and significance test is obtained that the results of the self-efficacy questionnaire and the descriptive question test are significant and linear. The correlation of the correlation moments obtained from rxy = 0.790 is used to test the hypothesis. It can be inferred from the findings of this investigation that the material of three-variable linear equation has a self-efficacy and the link between learning of mathematical results of a student.